PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL BERBASIS FILM DALAM PEMBELAJARAN PAI TERHADAP MOTIVASI BELAJAR SISWA KELAS V SDN TAMBAKSARI II KARAWANG - Nurhayati Nurhayati; Oyoh Bariah; Nur Aini Farida (Alifbata : Jurnal Pendidikan Dasar, 2025)
In PAI learning, using films as a learning medium can make learning easier and more enjoyable for students. Currently, students are starting to get bored with the same approach. The aim of this research is to describe the implementation of PAI learning using film-based audio-visual at SDN Tambaksari II Karawang. Knowing the influence of student learning motivation on the use of film-based audio visuals in PAI learning at SDN Tambaksari II Karawang. To determine the effect of using film-based audio visuals on student learning motivation in PAI subjects at SDN Tambaksari II Karawang. This research method uses a one group pretest posttest experimental design. Based on the results of the linearity test using the ANOVA table, it was found that there was a loose relationship between the pretest and posttest scores. This is shown by the significance value, namely in the Linearity section there is a significance value of less than 0.05, namely 0.048. And in the Deviation from Linearity section there is a significance value greater than 0.05, namely 0.222. This means that there is a linear relationship between the influence of film-based audio visuals and student learning motivation.  This improvement not only includes cognitive aspects but also affective aspects of students. This shows that films are a powerful tool to increase learning motivation and foster student love